Neuromuscular or Sensory Electrical Stimulation for Reconditioning Motor Output and Postural Balance in Older Subjects? - Paillard, Thierry (Frontiers in Physiology, 2022)
Percutaneous electrical stimulation is used for reconditioning functional capabilities in older sujects. However, its optimal application depends on the specific physiological needs of the individual. Depending on whether his/her needs are related to motor function or sensory and central functions, the relevant modality of electrical stimulation differs significantly. In fact, there are two main modalities of electrical stimulation, i.e., neuromuscular electrical stimulation (NMES) and sensory electrical stimulation (SES). NMES involves high intensity currents (above the motor threshold) and provokes involuntary visible direct muscle contractions. With chronic application, the induced adaptations occur mainly at the neuromuscular system level and thus enhance muscle strength and motor output. SES involves low intensity currents (below, at, or only just above the sensory threshold), does not induce any visible muscle contraction and provides only sensory information. With chronic application, the induced adaptations occur at the level of potentiation and transmission of proprioceptive afferents and thus facilitate sensorimotor activity (movement and balance). Overall, SES is interesting for the improvement/maintenance of sensorimotor capabilities in non-frail older subjects while NMES is relevant to develop muscle strength and thus reduce the risk of falls due to a lack of muscle strength in frail older subjects.